The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1074/jbc.m113.464503
|View full text |Cite
|
Sign up to set email alerts
|

Basal Autophagy Is Required for the Efficient Catabolism of Sialyloligosaccharides

Abstract: Background:The role of autophagy in glycan catabolism remains to be clarified. Results: In Atg5Ϫ/Ϫ cells, defective in autophagosome formation, sialyloligosaccharides accumulate specifically in the cytosol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…Autophagy is a conserved catabolic mechanism that protects cells by delivering potentially toxic macromolecular aggregates (e.g. proteins, lipids, and glycans) and damaged or superfluous organelles to lysosomes for degradation (1)(2)(3)(4)(5)(6). Various stimuli, such as starvation, endoplasmic reticular stress, DNA damage, and reactive oxygen species, may trigger autophagy.…”
Section: Hematopoietic Stem Cells (Hsc)mentioning
confidence: 99%
“…Autophagy is a conserved catabolic mechanism that protects cells by delivering potentially toxic macromolecular aggregates (e.g. proteins, lipids, and glycans) and damaged or superfluous organelles to lysosomes for degradation (1)(2)(3)(4)(5)(6). Various stimuli, such as starvation, endoplasmic reticular stress, DNA damage, and reactive oxygen species, may trigger autophagy.…”
Section: Hematopoietic Stem Cells (Hsc)mentioning
confidence: 99%
“…A putative POS-phosphatase activity was reported in the microsome fraction from human liver (14), but the molecular nature of this phosphatase is currently unknown. Moreover, we previously found that the induction of bulk autophagy by amino acid starvation reduces the levels of FNGs in the cytosol (34). Further studies will be needed to elucidate the molecular mechanism involved in the catabolism of small POSs.…”
Section: Discussionmentioning
confidence: 99%
“…Targets of autophagy can be specific proteins, nonspecific protein aggregates, or whole organelles, such as dysfunctional mitochondria. Basal autophagy is constitutive in most cell types (1)(2)(3), and it is estimated that basal autophagy is responsible for the catabolism of 1 to 1.5% of cellular proteins per hour even under nutrientrich conditions (4). However, because cell survival is constantly threatened by variations in both internal and external conditions, autophagy programs must be able to respond appropriately to stress.…”
Section: Introductionmentioning
confidence: 99%